Effect of Ground Cover Management on Nitrate Content and Lettuce (Lactuca sativa L.) Yield - Tošić Ivana; Červenski Janko; Govedarica Aleksandra Lučić (Contemporary Agriculture)
Ground cover management and woven agrotextile have an important role in lettuce production. However, there is limited information available on their combined effects. This research aimed to assess the influence of black and white geotextile mulching and woven agrotextiles used as plant cover on lettuce yield, soil nitrate content (N-NO3−) (kg ha−1) and nitrate content in lettuce leaves (mg kg−1). The experiment was set up as a randomized block design with six treatments, in four repetitions and three seasons, in the greenhouse and the open field in Banja Luka, Bosnia and Herzegovina. The applied soil mulching and plant covering treatments significantly increased lettuce yield in both greenhouse and open field. The highest lettuce yields were determined in the black geotextile treatment in both production systems. The N-NO3− content at a depth of 20-40 cm was on average four times higher in the greenhouse than in the open field. The nitrate content in lettuce leaves was on average 95.2% higher in the greenhouse production compared to the lettuce in the open field. The lowest N-NO3− content was recorded in the white geotextile treatment in the open field, while the use of black and white geotextile in the greenhouse led to the highest N-NO3- content in lettuce leaves.